The Role of Emotional Intelligence and Work Life Balance on Employee Performance PT Karya Padu Sejati Jakarta - Dellia Mila Vernia (Kirana Publisher (KNPub), 2023)
Employee performance itself is the result of work in terms of quality and quantity achieved by employees in carrying out the tasks assigned and in accordance with the responsibilities given. An employee's performance is not only assessed based on quantity, namely how much output is produced, time to complete the task, but is also assessed based on quality, including accuracy in work, ability to evaluate, employee abilities and skills, but there are many factors that influence employee performance. The aim of this research is to determine the influence of emotional intelligence and work life balance on employee performance at PT Karya Padu Sejati Jakarta. The method used is a quantitative method. Data was taken from filling in the questionnaire for variables The research results show that emotional intelligence influences employee performance, work life balance influences employee performance and emotional intelligence and work life balance influence employee performance at PT Karya Padu Sejati Jakarta. It is recommended that companies create self-control programs, such as having a spiritual shower at certain times.